Disaster risks in peri-urban areas of the great metropolitan area -past and recent considerations: guidelines and real scopes of risk management and land-use planning , Aserrí, Alajuelita, Desamparados, Escazú, Santa Ana and Mora cantons - Arroyo-González, Luis Nelson (2018)
To the southern part of San José city, there is a mountainous ridge that is the place where Aserrí, Desamparados, Alajuelita, Escazú, Santa Ana, and Mora cantons are settled. This area belongs to the old geological formation where, due to the rain pattern, the relief is affected by high weathering. This causes the presence of rugged hillsides. Since the nineties and due to its historic and geographical proximity to the central part of the country, this territory has been highly influenced by population growth and urbanization. The unrestricted way in which the population has occupied the land has caused landslides and flash floods. These processes are related to the physic dynamic of high slope reliefs and the way that many people are living over there.Keywords: